Castanea sativa mill. flowers as a source of bioactive phenolic compounds - Carocho, Márcio (2014)
In the Trás-os-Montes region of Portugal and across a good part of the Mediterranean countries, chestnut trees are a considerable part of the landscape. These trees and their respective nuts have been important in the past and are still a source of incomes for those regions. The chestnut tree and products, ·such as nuts, wood, leaves and flowers are known to possess a myriad of applications [1]. In particular, infusions and decoctions of chestnut flowers have been reported for different medical purposes [2], but their phytochemical profile and antioxidant activity are still mostly unknown. Herein, decoctions and infusions of flowers from the two most appreciated chestnut cultivars (longal and judia) in Trás-os-Montes, Portugal, were prepared and characterized with regard to their phenolic composition, which was analyzed by HPLC-DAD-ESI/MS. Furthermore, the antioxidant activity was assessed in terms of free radical scavenging capacity, reducing power and inhibition of lipid peroxidation in brain cell homogenates [2]. The individual polyphenol with the highest concentration in all samples was a trigalloyi-HHDP-glucoside, followed by pentagalloyl glucose, whereas quercetin 3-0-glucuronide and a quercetin hexoside were the most abundant flavonoids in judia and longal cultivars, respectively. The sample with the highest concentration of total polyphenols was the infusion of judia, closely followed by the decoction of longal. The preparations of the cultivar judia presented higher flavonoid levels than those of longal that in tern, displayed higher concentrations of hydrolyzable tannins. Decoctions showed greater antioxidant activity than infusions, which might be explained by the longer time at boiling point that decoctions were subjected to during extraction [2]. Overall, the decoction of the cultivar judia was the sample with both the highest quantity of flavonoids and antioxidant activity. The obtained results support ancestral claims about health benefits of infusions and decoctions of chestnut flowers. Moreover, due to the extremely potent antioxidant activity observed, flower decoctions are currently being tested for their potencial use as natural preservatives in food industry (research project PRODER n° 46577).